Elucidating Protein Translocon Dynamics with Single-Molecule Precision. Issue 7 (July 2021) - Davis, Madeline M.; Lamichhane, Rajan; Bruce, Barry D.
Abstract : Translocons are protein assemblies that facilitate the targeting and transport of proteins into and across biological membranes. Our understanding of these systems has been advanced using genetics, biochemistry, and structural biology. Despite these classic advances, until recently we have still largely lacked a detailed understanding of how translocons recognize and facilitate protein translocation. With the advent and improvements of cryogenic electron microscopy (cryo-EM) single-particle analysis and single-molecule fluorescence microscopy, the details of how translocons function are finally emerging. Here, we introduce these methods and evaluate their importance in understanding translocon structure, function, and dynamics. Highlights: Single-molecule Förster resonance energy transfer experiments have elucidated key details of the SecA-SecY translocation mechanism. Structural details of both post- and co-translational mechanisms have been resolved by cryogenic electron microscopy (cryo-EM), including the conformation of the co-translational quaternary complex and a post-translational translocation intermediate. Human disease mutants of Sec61 have been structurally resolved by cryo-EM, providing a foundation for understanding the role of the translocon-associated complex in some disorders. Detailed structural analysis of high-resolution cryo-EM structures of Tom40, a mitochondrial translocation channel, has led to an updated mechanistic model for preprotein entry and exit. Single-particle tracking has revealed the dynamics of plastid translocon components in vivo .